Preparation of polypropylene/ethylene‐propylene‐diene terpolymer/nitrile rubber ternary thermoplastics vulcanizates with good mechanical properties and oil resistance by core‐shell dynamic vulcanization. (20th May 2020) - Lv, Fei; Fan, Jianfeng; Huang, Jiarong; Cao, Liming; Yan, Xuesong; Ge, Ling; Abubakar, Saifudin; Chen, Yukun
Abstract : As the most successful commercialized thermoplastic vulcanizates (TPVs), polypropylene (PP)/ethylene propylene rubber (EPDM) TPVs exhibit poor oil resistance. In this work, we prepared PP/EPDM/butadiene acrylonitrile rubber (NBR) ternary TPVs with good oil resistance using core‐shell dynamic vulcanization. According to the theoretical analysis of the spreading coefficient and the transmission electron microscopy results, the rubber phases exhibited a special core‐shell structure, in which the cross‐linkedNBR‐core was encapsulated by the EPDM‐shell. The core‐shell structure effectively improved the interfacial compatibility between PP and NBR phase as the EPDM‐shell could avoid the direct contact of them, thus improving the mechanical properties of the TPVs. For example, the PP/EPDM/NBR (40/30/30) ternary TPV showed enhanced tensile strength of 12.57 MPa, compared with 10.71 MPa of PP/EPDM (40/60) TPV and 11.11 MPa of PP/NBR (40/60) TPV, respectively. Moreover, the oil resistance of the TPVs was also improved. Compared with PP/EPDM TPV, the change rates in mass, volume, tensile strength and elongation at break of PP/EPDM/NBR TPV after oil immersion decreased by 42.18%, 48.69%, 52.68% and 28.77%, respectively.